The n-th natural frequency for a medium with length L fixed at one end and free at the other end is given by the condition:
![L=(2n-1)/(4)\lambda_n](https://img.qammunity.org/2023/formulas/physics/college/k3jhzdvkehyqvs9p9cxepetj77csxsgvgu.png)
Where λ_n is the n-th natural wavelength. On the other hand, every transverse wave satisfies the following:
![v=\lambda f](https://img.qammunity.org/2023/formulas/physics/college/i838uwfyqotnoyo83z5m5nh9ah7vk1pyb2.png)
Where v is the speed of the wave, and f is the frequency of the wave.
Then:
![f_n=(v)/(\lambda_n)](https://img.qammunity.org/2023/formulas/physics/college/92j1f00g0trh19oi5vmhokwsmw4nb95utp.png)
Isolate 1/λ_n from the first equation:
![(1)/(\lambda_n)=(2n-1)/(4L)](https://img.qammunity.org/2023/formulas/physics/college/2kgk1rgsvjxvynorc8zxmcvwtonixwzqx0.png)
Then:
![f_n=(2n-1)/(4L)* v](https://img.qammunity.org/2023/formulas/physics/college/e21f7s7k5e1tk5gjheonmh3ke1nzhqyp9v.png)
Replace L=0.681m, v=25.5m and n=1,2,3 to fin the first three natural frequencies of the antenna:
![\begin{gathered} f_1=(2(1)-1)/(4*(0.681m))*25.5(m)/(s)\approx9.36Hz \\ \\ f_2=(2(2)-1)/(4*(0.681m))*25.5(m)/(s)\approx28.1Hz \\ \\ f_3=(2(3)-1)/(4*(0.681m))*25.5(m)/(s)\approx46.8Hz \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/qe15gvplx2q218qf4oh8kf3mrvzoy9obh6.png)
Therefore, the first three natural frequencies of the antenna are 9.36Hz, 28.1Hz and 46.8Hz.